Application of Ultraviolet Radiation to Control the Calcium Carbonate Scale Formation and Deposition on the Membranes. (23rd March 2020) - Basheer, Chanbasha; Rashwan, Mokhtar; Al-Mutairi, Eid; Shaikh, Amjad A.; Qureshi, Khurram Karim
Abstract : Scale formation on surfaces in contact with water supersaturated with calcium carbonate creates technical problems, including heat transfer hindrance, energy consumption, and equipment shutdown. Thus, nowadays, there is an increasing need for new approaches that are environmentally friendly and economically feasible. In this work, for the first time, calcium carbonate growth was investigated using UV light exposure, and the growth rate was compared with control and commercial antiscalant. Saturated calcium carbonate samples were exposed to UV radiation; the growth rate of calcium carbonate crystals was monitored at different time intervals. Results clearly show that about 85% decrease in crystal growth rate was observed when compared to 43% after the addition of 3 mg/L of amino tris(methylene phosphonic acid) antiscalant. Calcium carbonate scale deposition on hydrophobic and hydrophilic membranes was investigated. The amount of scale deposited in the case of a UV-treated sample is insignificant when compared to control samples. Thus, the exposure of UV might help to improve the membranes' lifetime. X-ray diffraction and scanning electron microscopy analyses revealed that UV light treatment produced mostly calcite crystals. The produced calcites are less dense and less adherent, and it can be easily removable when compared to other types of calcium carbonate phases. Thus, UV radiation is an efficient green approach for calcium carbonate scale mitigation on membrane surfaces.